"I Am Artistic": Mixed Method Case Study Research of Preservice Generalists' Perceptions of Arts in Education. (2nd July 2016) - Leonard, Alison E.; Odutola, Adeyanju O.
Abstract : Teacher education students not involved in the arts often claim to have negative assumptions about their arts abilities and a lack of experience when teaching in the arts. These negative perspectives contribute to their apprehension about engaging in arts practices with future students. This article presents mixed methods case study findings exploring changes in student perceptions throughout an arts in education course for education majors. This study considers the influences of space, pedagogy, modes of engagement, and content on changes in perceptions. Data collection involved Likert questionnaires, along with course portfolios. Utilizing the emergent qualitative analytical lens of crystallization to illuminate a complex picture of experiences within this specific arts in education context, students' perceptions of the role of the arts in education and their own artistic abilities were seen to increase, also noting positive perceptions of the physical classroom space in which the course takes place.